Schaum's outline of theory and problems of college mathematics algebra, discrete mathematics, trigonometry, geometry, introduction to caculus - Ayres, Frank (Schaum's outline series, 1992)
Contains a review of basic algebra, college algebra and analytic geometry, trigonometry, discrete mathematics, and calculus.